Imitation under stress - Magdalena Buckert; Jörg Oechssler; Christiane Schwieren (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2014)
Imitating the best strategy from the previous period has been shown to be an important heuristic, in particular in relatively complex environments. In this experiment we test whether subjects are more likely to use imitation if they are under stress. Subjects play a repeated Cournot oligopoly. Treatments are time pressure within the task and distractions through a second task (a Stroop-task) that has to be performed as well and influences payment. We measure stress levels through salivary cortisol and heart rate. Our main findings are that time pressure and distraction can indeed raise physiological stress levels of subjects within our task. More importantly from an economic perspective, we can also observe a corresponding behavioral change that is indicative of imitation.
Keywords: C91; C72; D74; 330; stress; cortisol; heart rate; imitation; experiment